Agent-based framework for modeling and simulation of resources in self-sustainable human settlements: a case study on water management in an eco-village community in Croatia. Issue 6 (1st November 2016) - Tomičić, Igor; Schatten, Markus
ABSTRACT: A newly developed agent-based framework for modeling, simulation, and evaluation of resource management in self-sustainable human settlements is presented, along with the ability of the framework to prolong the self-sustainability of the observed human settlement system in the simulation environment. In this study the focus is on the analysis of a conducted water management simulation based on observations of an existing eco-village in Croatia, in the context of producing, storing, and consuming water as a resource. The conducted research shows that the developed framework was able to prolong the self-sustainability of localized water production, storage, and consumption dynamics when managing the water allocation with the use of self-sustainability mechanisms, in comparison to water management without using such mechanisms, under the same initial conditions. The work is placed within the context of sustainable development, Internet of Things, as well as Environmental Internet of Things areas of research, analyzing the ambiguous relationship between the terms 'sustainable development' and 'self-sustainability'.